1992
DOI: 10.1128/aac.36.7.1441
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the human immunodeficiency virus reverse transcriptase residues that contribute to the activity of diverse nonnucleoside inhibitors

Abstract: The reverse transcriptase (RT) of human immunodeficiency virus type 1 (HIV-1) is potently inhibited by a structurally diverse group of nonnucleoside compounds. These include pyridinone derivatives, tetrahydroimadazo[4,5,1-j,k][1,4]-benzodiazepin-2(1H)-one and -thione, and BI-RG-587 (nevirapine). The compounds act noncompetitively, by an unknown mechanism, with respect to template-primer and nucleotide substrates. Despite a high degree of similarity between the HIV-1 and HIV-2 RTs, the HIV-2 enzyme is totally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…Condra et al (10) recently reported on molecular interactions between the nonnucleoside RT inhibitors and a region of the RT molecule defined by amino acid residues 176 to 190, with specific contributions by the tyrosines at positions 181 and 188. In order to determine whether the amino acid residues at positions 181 and 188 were involved in the inhibitory activity of michellamine B, we utilized two HIV RT mutants with single amino acid substitutions at these positions (5).…”
Section: Discussionmentioning
confidence: 99%
“…Condra et al (10) recently reported on molecular interactions between the nonnucleoside RT inhibitors and a region of the RT molecule defined by amino acid residues 176 to 190, with specific contributions by the tyrosines at positions 181 and 188. In order to determine whether the amino acid residues at positions 181 and 188 were involved in the inhibitory activity of michellamine B, we utilized two HIV RT mutants with single amino acid substitutions at these positions (5).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of drug required to inhibit viral replication by 50% in a single-cycle assay was determined with reference to that for a drug-sensitive reference strain (CNDO) containing PR and RT coding sequences from laboratory HIV strain NL4-3. Overall, the assay is reproducible within a 2.5-fold range (17). A panel of 15 ARV drugs were used in the PhenoSense HIV assay.…”
Section: Methodsmentioning
confidence: 99%
“…The TIBO compounds interact with the HIV-1 reverse transcriptase molecule at a site distinct from that utilized by the nucleoside triphosphate, primer, or template (Goldman et al, 1991;Wu et aI., 1991;Debyser et aI., 1992;Dueweke et al, 1992). The specificity of the TIBO analogues for HIV-1 appears to resultfrom the tertiary structure ofthe HIV-1 RT molecule (Shih et aI., 1991;Condra et al, 1992) and binding of the agents to the enzyme may only occur after unfolding of the binding region. Other non-nucleoside inhibitors of HIV-1 reverse transcription described apparently bind in the same pocket of HIV-1 reverse transcriptase and have an antiviral spectrum similar to the TIBO compounds (Merluzzi et al, 1990;Goldman et aI., 1991;Romero et al, 1991;Camarasa et aI., 1992;Klunder et aI., 1992;Buckheit et aI., 1993;McMahon et al, 1993).…”
Section: Introductionmentioning
confidence: 99%